Performance of wheat varieties grown from seeds with different vigor levels - Koch, Felipe; Andrade Monteiro, Manoela; Garbin Martinazzo, Emanuela; Mengue Rolim, Jessica; Pedó, Tiago; Zanatta Aumonde, Tiago (Revista Ceres, 2022)
The objective of this study was to evaluate the performance of wheat plant grown from seeds with different vigor levels. The experimental design was randomized blocks in a 3 x 3 factorial design (cultivar x vigor level) with four replications. The wheat cultivars were Tbio Toruk, Tbio Mestre and Tbio Iguaçu. The classification of vigor levels was high, medium and low, determined by several vigor procedures. The following evaluations were performed: plant height, number of spikelets in the main tiller, number of seeds in the main tiller, seed mass in the main tiller, number of fertile tillers, number of seeds in tillers, seed mass in tillers, number of plants.m-2, number of spikes.m-2, and grain yield per hectare. The use of high vigor seeds provides a greater number of wheat plants and spikes per area. Grain yield is affected significantly by seed vigor level: there is an increase of up to 11% by using high vigor seeds compared to low vigor seeds.